SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN BANTUAN BEASISWA TIDAK MAMPU DENGAN METODE SAW (Studi Kasus SD Muara Mea) - Wulandari, Lasri (Universitas Multi Data Palembang, 2024)
Scholarships are financial support provided by various parties such as governments, private companies, embassies, universities, and educational institutions, rather than coming from personal or parental sources. In order for scholarship distribution to be carried out more precisely, the selection of scholarship recipients by educational institutions must be improved. One of the methods used is Simple Additive Weighting (SAW), where this method involves summing the weights of the ratings on each alternative. This study aims to build a decision support system in the selection of recipients of scholarship assistance at SD Muara Mea using the Simple Additive Weighting (SAW) method. Based on testing done using 15 data, it produces a system accuracy value with a percentage of 66%.